KONSEP DAN IMPLEMENTASI CINTA: STUDI KOMPARASI PEMIKIRAN IMAM GHAZALI DAN ERICH FROMM - Mas Rukhin Lubabul; M. Lutfi Mustofa; Zainal Habib (Academic Journal of Islamic Principles and Philosophy, 2025)
Human life is inextricably linked to love, whether it is needing or giving love to oneself or to others, because in order to achieve happiness, humans need love. The purpose of this article is to compare the concept of love in the views of Imam Ghazali and Erich Fromm, both of whom are leading figures in the fields of Sufism and existentialist philosophy. This article uses a qualitative research method with a literature review approach sourced from books, articles, and information data relevant to the discussion of the concept of love. The results of this study are as follows: First, the concept of love in Imam Ghazali's view means enjoyment that requires effort. Love for Allah is absolute love through the medium of love for oneself, love for fellow human beings, and love for the beauty created by Allah. Second, the concept of love in Erich Fromm's view is one of the solutions to overcome feelings of separation and alienation. Third, the implementation of love for fellow human beings in Imam Ghazali's view means that every human being must behave fairly, be forgiving, give advice, and be generous, which is manifested in human relationships. Meanwhile, in Erich Fromm's view, love for fellow human beings can be manifested in the form of knowledge, respect, care, and responsibility.